PENGARUH STRUKTUR MODAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2017 - Abdul Hadi Sirat; Muhsin N Bailusy; Dian Kurnia (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2019)
This study aims to determine the effect of capital structure and institutional ownership on firm value with dividend policy as an intervening variable. In manufacturing companies listed on the Indonesia Stock Exchange with a sample of 39 companies. The analytical method used is path analysis. The observation period for 5 years and the research data are secondary data obtained from www.idx.co.id.The results showed that the direct effect of capital structure variables (DER) had a negative and significant effect on firm value, institutional ownership variables (INST) had a negative and significant effect on firm value, dividend policy (DPR) had a positive but not significant effect on firm value. While the indirect effect of capital structure (DER) on firm value (INST) through dividend policy (DPR) is that dividend policy cannot mediate the effect of capital structure on firm value and indirect influence of institutional ownership (INST) on firm value (INST) through dividend policy (DPR) is that dividend policy cannot mediate the effect of institutional ownership (INST) on firm value (INST)